Detecting Potential Overbilling in Medicare Reimbursement via Hours Worked: Comment - Matsumoto, Brett (American Economic Review, 2020)
Fang and Gong (2017) develop a procedure to detect potential over-billing of Medicare by physicians. In their empirical analysis, they use aggregated claims data that can overstate the number of services performed due to features of Medicare billing. In this comment, I show how auditors can use detailed claims-level data to better target improper overbilling. (JEL H51, I13, I18, J22, J44)